Wars on terrorism and Iraq : human rights, unilateralism, and U.S. foreign policy - Weiss, Thomas G. (Thomas George), 1946-; Crahan, Margaret E.; Goering, John M. (Routledge, 2004)
Wars on Terrorism & Iraq provides a timely and critical analysis of the impact of the wars on terrorism and Iraq on human rights particularly internationally, as well as related tensions between unilateralism and multilateralism in U.S. foreign policy. The distinguished contributors examine the consequences for international relations and world order of the traditional standard bearer for human rights and democracy (the United States) appearing not to be championing the rule of law and negotiated conflict resolution. The authors also suggest effective policies to promote greater fulfillment of human rights in order to achieve peaceful accord within nations and stability internationally.